2006
DOI: 10.1093/jee/99.4.1214
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlation of Fitness with Group Size in Two Biotypes of Russian Wheat Aphid (Homoptera: Aphididae)

Abstract: Changes in Þtness parameters as a function of colony size (one versus 10 aphids) were measured in two biotypes (RWA1 and RWA2) of the Russian wheat aphid, Diuraphis noxia (Mordvilko) (Homoptera: Aphididae), feeding on three cultivars of wheat, Triticum aestivum L., at two temperatures. ÔTregoÕ is a cultivar with no speciÞc resistance to D. noxia, whereas, ÔStantonÕ and ÔHaltÕ express Dny and Dn4 resistance sources, respectively. Feeding in a group accelerated the development of RWA1 on Trego and Stanton at 20Њ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…For example, it could be that by mixing, the aphids would be able to more easily build up a large colony, which would more likely be tended by ants (Stadler et al. 2003), that they could obtain benefits via a predator dilution effect (Turchin & Kareiva 1989; Krause & Ruxton 2002), that they could use the presence of other aphids as cues to find the best feeding sites or seek out plants with little aphid resistance and poor chemical defences (Fletcher 2006), or that they could affect plant metabolism in a way that would result in enhanced food availability and higher aphid growth rates when they occurred in small groups (Way & Banks 1967; Dixon & Wratten 1971; Qureshi & Michaud 2005; Michaud et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it could be that by mixing, the aphids would be able to more easily build up a large colony, which would more likely be tended by ants (Stadler et al. 2003), that they could obtain benefits via a predator dilution effect (Turchin & Kareiva 1989; Krause & Ruxton 2002), that they could use the presence of other aphids as cues to find the best feeding sites or seek out plants with little aphid resistance and poor chemical defences (Fletcher 2006), or that they could affect plant metabolism in a way that would result in enhanced food availability and higher aphid growth rates when they occurred in small groups (Way & Banks 1967; Dixon & Wratten 1971; Qureshi & Michaud 2005; Michaud et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…RWA1 performed better on the susceptible Trego than on either of the two resistant cultivars, ÔStantonÕ and ÔHalt,Õ whereas RWA2 performed well on all three cultivars and formed larger colonies. Michaud et al (2006) also found a reduced performance of RWA1 on resistant cultivars, with reproductive rate reduced on resistant cultivars by an average of 32 and 41%. Hossein (2010) found signiÞcant differences in r m values of Russian wheat aphid on Þve varieties of wheat, and he concluded that varieties with the highest r m value were susceptible and those with the lowest r m values were considered to be resistant varieties.…”
Section: Resultsmentioning
confidence: 83%
“…From the results, it can be concluded that the different biotypes have different reproductive ability, and therefore ability to survive, on different host plants. The reproductive and development rates of Russian wheat aphid are inßuenced by various different factors, such as temperature (Aalbersberg et al 1987), host plant growth stage (Girma et al 1990), host quality , aphid biotype , population density (Michaud et al 2006), and feeding site on the plant (Stary 1999). Michaud et al (2006) also found signiÞcant effects of biotype on reproductive life and that the number of offspring produced by females was inßuenced by interactions between biotype, grouping, temperature, and cultivar.…”
Section: Resultsmentioning
confidence: 99%
“…Clipper plants and were kept in insect cages in separate controlled environment cabinets (Conviron) (Saheed et al., 2007a). Careful quarantine procedures were observed while handling the aphids in order to prevent cross‐contamination of biotypes (Michaud et al., 2006).…”
Section: Methodsmentioning
confidence: 99%